Reframing sustainable development through Islamic futures thinking: ethical foundations and strategic implications - Jalal Nori, Abdulwahed; Altabaa, Homam (Doha International Center for Interfaith Dialogue, 2025)
This article offers a critical exploration of the epistemological and ethical convergence between Islamic principles and the United Nations Sustainable Development Goals (SDGs), examined through the integrative framework of futures thinking. Employing the metaphor of roots, branches, and bridges, it articulates how Islamic epistemology—anchored in tawḥīd (divine unity), maqāṣid al-sharīʿah (the higher objectives of Islamic law), and khilāfah (human vicegerency)—provides a comprehensive and anticipatory paradigm for addressing sustainability, environmental responsibility, and global equity. The analysis advances the argument for the recognition and integration of faith-based knowledge systems within global development discourse, highlighting the indispensable role of ethical foresight, metaphysical intentionality, and moral vision in shaping long-term strategies. By reframing the SDGs as more than technocratic targets, the article positions them as a potential platform for cultivating intergenerational justice and spiritually grounded transformation.